2022
DOI: 10.1186/s12933-021-01437-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of interleukin-12/23p40 may serve as a potential indicator of dysfunctional heart rate variability in type 2 diabetes

Abstract: Background Systemic inflammatory processes plausibly contribute to the development of cardiovascular complications, causing increased morbidity and mortality in type 2 diabetes. Circulating inflammatory markers, i.e., interleukin (IL)-6 and tumour necrosis factor-α, are associated with neurocardiac measures. We examined a broad panel of various inflammatory and inflammation-related serum markers to obtain more detailed insight into the possible neuro-immune interaction between cardiovascular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…have shown that elevated levels of interleukin-12 may serve as a potential indicator of dysfunctional heart rate variability in diabetic patients. [ 31 ] Our study shows significant arrhythmia and ECG changes in this population and is essential for primary care and emergency physicians dealing with COVID-19 to be prepared to arrhythmic cardiac emergencies in this subset of patients. Further studies with IL-6 levels and cardiac imaging need to be done to look for structural effects and also studies to look at whether anticytokine therapies can reverse these adverse effects.…”
Section: Discussionmentioning
confidence: 93%
“…have shown that elevated levels of interleukin-12 may serve as a potential indicator of dysfunctional heart rate variability in diabetic patients. [ 31 ] Our study shows significant arrhythmia and ECG changes in this population and is essential for primary care and emergency physicians dealing with COVID-19 to be prepared to arrhythmic cardiac emergencies in this subset of patients. Further studies with IL-6 levels and cardiac imaging need to be done to look for structural effects and also studies to look at whether anticytokine therapies can reverse these adverse effects.…”
Section: Discussionmentioning
confidence: 93%
“…Initial findings showed a significant negative correlation between ICAM‐1 and SDANN (Standard deviation of the average NN intervals), rMSSD (Root mean square of successive RR interval differences), VLF (Very low frequency), or LF (Low frequency), demonstrating a correlation between decreased parasympathetic and sympathetic activity and elevated ICAM‐1 levels. Crucially, the statistical significance of the link between SDANN and the variable of interest remained even after controlling for demographics, diabetes‐related variables, and cardiovascular risk factor 69 …”
Section: Icam‐1 and Cvdmentioning
confidence: 95%
“…Crucially, the statistical significance of the link between SDANN and the variable of interest remained even after controlling for demographics, diabetes-related variables, and cardiovascular risk factor. 69 In another study, Herder et al studied the relationship between ICAM-1 and HRV measures in T2DM patients. The initial data revealed a substantial negative connection between ICAM-1 and SDANN, rMSSD, VLF, and LF, implying that increased ICAM-1 levels were associated with lower parasympathetic and sympathetic activity.…”
Section: Metabolic Abnormalities and Icam-1mentioning
confidence: 99%
“…Moreover, systemic low-grade inflammation is associated with objective measures of commonly diagnosed complications such as distal symmetrical polyneuropathy and diabetic autonomic neuropathy [ 9 , 10 ]. Consequently, circulating biomarkers may reflect local neuroinflammation in diabetes [ 11 , 12 , 13 ], and it is plausible that systemic inflammation also impairs the enteric nervous system, thereby deteriorating motility in diabetes, causing gastroenteropathy.…”
Section: Introductionmentioning
confidence: 99%